A study of the energy cost of activities and dietary intake of non-working mothers living in a low-income urban community ; Demetria C. Bongga , adviser. - Caridad, Josefina Teresita 1959- ([s.n.], 1987)
Nine unemployed mothers living in a low-income, urban community were studied to determine their pattern of daily activity, dietary intake, and energy expenditure. Measurement of actual energy expended for various activities were done by indirect calorimetry using the Kofranyi-Michaelis respirometer. The mean total energy expenditure was 1,824 kcal/day. Based on this, the mothers were classified as moderately active to very active since they spentt about 40 kcal/kg DBW/day. Assessment of food intake indicated a mean of 1,835 kcal/day. The differences between the food intake and energy expenditure of mothers were, however, not significant.